2018
DOI: 10.1002/jmri.26022
|View full text |Cite
|
Sign up to set email alerts
|

T2* Mapping to characterize intestinal fibrosis in crohn's disease

Abstract: 1 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…As the study was conducted retrospectively, we were not able to quantify perfusion by CMR or verify the relation between T2* and fibrosis in histopathologic analyses. However, studies from different tissues have already shown a correlation between T2* values and collagen or LGE [14,[16], [17], [18]]. In addition, microvascular dysfunction in HCM has already been described in literature and perfusion studies in CMR have shown good accuracy for the description of microvascular dysfunction [8,12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As the study was conducted retrospectively, we were not able to quantify perfusion by CMR or verify the relation between T2* and fibrosis in histopathologic analyses. However, studies from different tissues have already shown a correlation between T2* values and collagen or LGE [14,[16], [17], [18]]. In addition, microvascular dysfunction in HCM has already been described in literature and perfusion studies in CMR have shown good accuracy for the description of microvascular dysfunction [8,12].…”
Section: Discussionmentioning
confidence: 99%
“…However, in terms of further structural characterization and because not all HCM patients are able to receive contrast agents due to contraindications such as renal failure, T2* magnetic relaxation parameters (parametric mapping) have been exploited to visualize mesoscopic (structure of the tissue) magnetic field inhomogeneities [[13], [14], [15]]. For instance, T2* was demonstrated to characterize fibrosis in extracardiac tissues such as the intestinal tract, but also in ischemic and fibrotic segments after myocardial infarction [[15], [16], [17], [18]]. In addition, histopathologic substrates of T2* and a correlation of T2* to flow analyses have already been studied in affected tissues [16,17,19,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, reduced T2* values have already shown the potential to describe structural alterations suggestive of ischaemic alterations, collagen areas or haemorrhage in cardiac and extracardiac tissues 15 18 21. According to this, histopathological substrates of T2* and a correlation of T2* to flow analyses have been studied 16 17 19 20 30. Recently, reduced T2* values have been described in a group of patients with HCM potentially triggered through relative ischaemia 22.…”
Section: Discussionmentioning
confidence: 99%
“…CMR is able to detect myocardial alterations and relative ischaemia using contrast agent and parametric mapping 6 13–15. In particular, T2* mapping has proven feasibility to detect ischaemic segments in extracardiac organs but also in myocardial infarction and coronary artery disease (CAD) 15–21. Reduced T2* values have been described in patients with HCM potentially triggered through relative ischaemia 22.…”
Section: Introductionmentioning
confidence: 99%